Company taxation. - Bond, S; Klemm, A; Simpson, H (IFS, 2004)
This chapter cover two topics – corporate tax reform and issues arising from the introduction of the 0% starting rate of corporation tax in April 2002. Since 1997, the government has made some substantial reforms to the UK corporation tax system. In recent years, it has been consulting on further reform. Section 6.1 provides some background to the debate and discusses the main proposals for reform. Section 6.2 looks at a specific tax change – the introduction of the 0% corporation tax rate for companies with taxable profits of less than £10,000. It discusses the incentives created by this tax change for individuals to set up incorporated businesses, and in particular the incentives faced by self-employed individuals to incorporate.